Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. A proposed vision for the role of Saudi universities in developing and enhancing the intellectual security of their students Dr. Aisha Ali Msoud Asiri 2. The Degree of Application of Administrative Accountability among Government School principals in the schools of the Yatta Directorate of Education from the point of view of Teachers Mr. Ibrahim Musallam Makhamreh, Ms. Rasha Yasser Alyan 3. Digital transformation in the use of artificial intelligence in education for smart schools in Jenin Governorate Ms. Inas Fuad AbuFarhah, Dr. Maher Fuad AbuFarhah 4. Scientific parks in some countries and the possibility of benefiting from them in the Kingdom of Saudi Arabia Ms. Hanan Nour Al-Solami, Co-Prof. Mona Muhammad Alsanee 5. The criteria for nominating gifted coordinators in public and private schools and their effects on talent sustainability: A mixed study Ms. Albandary Abdullah Alhassan, Dr. Abdulhamid Alarfaj 6. Developing the leadership competencies of department heads in Saudi universities in light of the human capacity development program Mr. Ali Yahya Garrah 7. The relationship of quality of life to the level of ambition in light of some variables among students at the College of Educational Sciences, Mu’tah University Mr. Fahd Hamad Al-Nuaimi 8. Requirements for the Implementation of Cyber Security in Nizwa University in light of Oman Vision 2040 and its obstacles from the point of view of academics and employees Ms. Najla Moosa Mohammed Al-Balushi, Ms. Teeba Saif Ahmed Al-Rawahi, Ms. Badriya Hamood Said Al-Aamri, Dr. Rabia Al-Mur Ali Al-Dhuhli, Dr. Hamed Hilal Hamood Al-Yahmadi, Dr. Mohammed Ismail Abdullah Al-Qudah